2014
DOI: 10.1007/s10339-014-0630-4
|View full text |Cite
|
Sign up to set email alerts
|

Simulating bistable perception with interrupted ambiguous stimulus using self-oscillator dynamics with percept choice bifurcation

Abstract: A behavioral stochastic self-oscillator model is used for simulating interrupted ambiguous stimulus-induced percept reversals. The results provide further support for a dynamical systems foundation of cognitive and psychological problems as discussed in detail within the context of Gestalt psychology by Wagemans et al. (Concept Theor Found Psychol Bull 138(6):1218-1252, 2012), and for coordination dynamics of the brain (Kelso in Philos Trans R Soc B 367:906-918, 2012). Statistical evaluation of simulated rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Several findings indicate that adaptation plays a role in shifts of perception: in simple terms, neurons for one interpretation become adapted or fatigued to a point where they are less excited than neurons for the alternative interpretation, which then take over (Gómez et al, 1995). Recent papers have developed theoretical models of reversibility in bistable percepts that have proposed processes specific to the phenomenon (Furstenau, 2014; Lee, 2014; and see also Holcombe & Seizova-Cajic, 2008). Thus, the time scale of, and effects of manipulated variables on, perceptual reversals reflects, not a general temporal integration process constructing the “subjective present,” but a specific feature of visual processing (fatigue or adaptation) that happens to occur on a similar (though not identical) time scale.…”
Section: Review Of Researchmentioning
confidence: 99%
“…Several findings indicate that adaptation plays a role in shifts of perception: in simple terms, neurons for one interpretation become adapted or fatigued to a point where they are less excited than neurons for the alternative interpretation, which then take over (Gómez et al, 1995). Recent papers have developed theoretical models of reversibility in bistable percepts that have proposed processes specific to the phenomenon (Furstenau, 2014; Lee, 2014; and see also Holcombe & Seizova-Cajic, 2008). Thus, the time scale of, and effects of manipulated variables on, perceptual reversals reflects, not a general temporal integration process constructing the “subjective present,” but a specific feature of visual processing (fatigue or adaptation) that happens to occur on a similar (though not identical) time scale.…”
Section: Review Of Researchmentioning
confidence: 99%
“…Meng and Tong instructed subjects to hold one of the two rival stimuli dominant for as long as possible 50 . The results showed only a weak and statistically unreliable attentional modulation effect over the dynamics of BR, in contrast to the strong attention modulation effects observed in studies of perceptual reversals for other bistable stimuli 50–52 . Moreover, Chong et al.…”
Section: Discussionmentioning
confidence: 90%
“…50 The results showed only a weak and statistically unreliable attentional modulation effect over the dynamics of BR, in contrast to the strong attention modulation effects observed in studies of perceptual reversals for other bistable stimuli. [50][51][52] Moreover, Chong et al found that enhancing task relevance of a rival stimulus (e.g., directing observers' attention to a changing feature of that stimulus) can lengthen perceptual dominance. 53 These attentional modulation effects are not applicable to the current research, as neither voluntary control nor task-driven attentional selection was involved in our behavioral task (i.e., color discrimination).…”
Section: Other Possible Mechanisms Underlying the Temporal Structure ...mentioning
confidence: 99%
“…Previously, there have been many attempts to account for bistable perception phenomena ranging from dynamical systems models ( Fürstenau 2007 , 2010 , 2014 ) through to predictive processing frameworks ( Dayan 1998 ; Hohwy et al. 2008 ; Brascamp et al.…”
Section: Computational Accounts Of Bistable Perceptionmentioning
confidence: 99%